Respuesta :
the quotient of -1 4/5 and 3 1/4 = (-1 4/5) / ( 3 1/4)
= [ - (5 * 1 + 4) / 5 ] / [ (3 * 4 + 1) / 4 ]
= [ -9 / 5 ] / [ 13 / 4 ]
= [ -9 / 5 ] * [ 4 / 13 ]
= [ -9 * 4 ] / [ 5 * 13 ]
= -36/65
another way is to do it separately first: -1 4/5 and 3 1/4
-1 4/5 = -(1 + 4/5)
= -(5/5 + 4/5)
= -9/5
3 1/4 = 3 + 1/4
= 3*4/4 + 1/4
= 12/4 + 1/4
= 13/4
so (-1 4/5) / ( 3 1/4)
= (-9/5) / (13/4)
= (-9/5) * (4/13)
= (-9*4) / (5*13)
= -36/65
= [ - (5 * 1 + 4) / 5 ] / [ (3 * 4 + 1) / 4 ]
= [ -9 / 5 ] / [ 13 / 4 ]
= [ -9 / 5 ] * [ 4 / 13 ]
= [ -9 * 4 ] / [ 5 * 13 ]
= -36/65
another way is to do it separately first: -1 4/5 and 3 1/4
-1 4/5 = -(1 + 4/5)
= -(5/5 + 4/5)
= -9/5
3 1/4 = 3 + 1/4
= 3*4/4 + 1/4
= 12/4 + 1/4
= 13/4
so (-1 4/5) / ( 3 1/4)
= (-9/5) / (13/4)
= (-9/5) * (4/13)
= (-9*4) / (5*13)
= -36/65
Here, Expression: (-1 4/5)/(3 1/4)
= (-9/5)/(13/4)
We can re-write it as:
= -9/5 * 4/13
= -36/65
In short, Your Answer would be: -36/65
Hope this helps!
= (-9/5)/(13/4)
We can re-write it as:
= -9/5 * 4/13
= -36/65
In short, Your Answer would be: -36/65
Hope this helps!